Physical Touch Code Sistem Pengaman Sepeda Motor Menggunakan GPS - Muhammad Faezal Ferdhiansyah; Noor Yulita Dwi Setyaningsih; Mohammad Dahlan (UNIB Press, 2023)
Motorcycle thefts that are rife in the neighborhood give rise to concerns that simply locking a motorcycle is not enough. With the advancement of technology, we can develop a security system on motorcycles to reduce theft rate. In the case of motorcycle theft, there are two motives for theft, including the ignition key that has been forgotten to be removed and the motorcycle contact jacked up with a key letter T. Researchers designed a physical touch code motorcycle security system using GPS which aims to monitor motorbikes using a smartphone in the event of theft. The method used in this research is Research And Development. Telegram is used for monitoring motorbikes. The results of the research have made a physical touch code device for a motorbike security system using GPS. Physical touch code can create security. Telegram alarms and notifications can work properly. Telegram can receive notifications if in contact condition on ≥ 9 seconds the secret touch point is not touched with a horn sound delay with notifications received an average of 2 seconds. Keywords: ESP32; IoT, Security System, Telegram.